Previsit Patient Instructional Video for the Virtual Orthopedic Foot and Ankle Examination. Issue 3 (7th July 2021) - Noori, Naudereh; Chien, Bonnie; Zhang, Zijun; Schon, Jason; Hembree, Walter; Schon, Lew
: Level of Evidence: Level V, clinical tips.